PERANCANGAN WEBSITE LESCATUR BERBASIS VIRTUAL STUDENT-CENTERED LEARNING - I Gede Wahyu Dipta Pariandika; Daniel Wijaya; Jason Nicholas Winata; Angelina Salim; Muhammad Arsyah Albasam (STKIP PGRI Situbondo, 2026)
In an era of rapid technological development, chess education remains rigid and often fails to adapt to the diverse abilities of individual learners. To address this gap, Lescatur was developed as a student-centered chess learning platform that offers comprehensive features, including personal coaching. This study adopts a design-thinking approach, utilizing surveys to identify user needs and expert validation through CVR and CVI to assess the essentiality and relevance of the prototype features. A total of 73 respondents participated in the user-needs survey, focusing on expectations for digital chess learning. Expert validation involved five specialists who evaluated key features such as personal coaching, AI training modules, interactive e- books, and instructional videos. Survey findings indicate a strong demand for personalized and adaptive chess learning, positioning Lescatur as a potential solution for comprehensive and flexible digital chess education. The purposes of this study include (1) identifying user needs (empathize), (2) defining core learning problems (define), (3) generating interactive and adaptive learning concepts (ideate), (4) developing the prototype (prototype), and (5) evaluating its user experience (test). The CVR and CVI results demonstrate strong content validity, with nearly all CVR items meeting the minimum threshold of 0.99 and the S-CVI average exceeding 0.9, indicating high expert agreement regarding essentiality and relevance. These findings support the feasibility of further developing the Lescatur platform as a valid and user-centered virtual chess learning solution.